Effects of heat‐assisted irradiation treatment on microbial and physicochemical qualities of dried laver (Porphyra spp.) and optimization by response surface methodology. (28th November 2018) - Lee, Eun‐Jin; Ameer, Kashif; Jo, Yunhee; Kim, Gui‐Ran; Kyung, Hyun‐Kyu; Kwon, Joong‐Ho
Abstract: The Korean Food Code has approved irradiation less than 7 kGy for microbial control in algal food, which is often not sufficient to achieve the acceptable contamination level (<10 4 CFU/g). In this study, heat‐assisted low‐dose electron beam (E‐beam) irradiation was applied for improving the microbial quality of dried laver through the response surface optimization of process conditions (Xn); irradiation dose (0–4 kGy, X1), heating temperature (140–180°C, X2) and heating time (0–28 s, X3) for their effects on total aerobic bacteria (TAB) count, moisture content, chlorophyll content, carotenoid content and overall palatability of dried laver. TAB counts were affected more by irradiation dose than by heating temperature and time. Moisture, chlorophyll and carotenoid content and overall palatability were more affected by heating temperature and heating time than by irradiation dose. The overall results indicated that the optimal conditions were irradiation dose of 1.8–3.0 kGy, heating temperature of 154–170°C and heating time of 10–18 s to achieve appropriate quality attributes of heat‐assisted E‐beam irradiated dried laver, such as TAB count of 10 3 CFU/g, moisture content of 5% and 6.5 of good overall palatability score out of 7.